Two-dimensional ultrathin Ti3C2 MXene nanosheets coated intraocular lens for synergistic photothermal and NIR-controllable rapamycin releasing therapy against posterior capsule opacification - Ye, Zi; Huang, Yang; Li, Jinglan; Ma, Tianju; Gao, Lixiong; Hu, Huihui; He, Qing; Jin, Haiying; Li, Zhaohui (Frontiers in Bioengineering and Biotechnology, 2022)
Posterior capsule opacification (PCO) is one of the most frequent late-onset complications after cataract surgery. Several kinds of drug-eluting intraocular lens (IOL) were designed for sustainable drug release to suppress ocular inflammation, proliferation of lens epithelial cells (LECs) and development of PCO after cataract surgery. Nevertheless, the drug-loaded IOLs were limited in ocular toxicity, insufficient drug-loading capacity, and short release time. To prevent PCO and to address these drawbacks, a novel drug-loaded IOL (Rapa@Ti3C2-IOL), prepared from two-dimensional ultrathin Ti3C2 MXene nanosheets and rapamycin (Rapa), was fabricated with a 2-step spin coating method in this study. Ti3C2 was as a drug delivery reservoir of Rapa. Rapa@Ti3C2-IOL was designed to have the synergistic photothermal and near infrared (NIR)-controllable drug release property. As a result, Rapa@Ti3C2-IOL exhibited the advantages of simple preparation, high light transmittance, excellent photothermal conversion capacity, and NIR-controllable drug release behavior. Rapa@Ti3C2-IOL showed photothermal ablative, anti-proliferative, anti-migratory and anti-inflammatory effects in vitro. In a chinchilla rabbit model of cataract surgery, Rapa@Ti3C2-IOL effectively prevented PCO development and ocular inflammation under a mild NIR power density (1.0 W cm-2) with good biocompatibility. In summary, the present study offers a promising strategy for preventing PCO via ultrathin Ti3C2 MXene nanosheet-based IOLs with synergistic photothermal and NIR-controllable Rapa release properties.